Let's get physical. (22nd December 2017) - Ellis, Thomas
Abstract : The consensus in philosophical and scientific circles is that physicalism is the most warranted position to adopt. With respect to the academic study of religion, physicalism underwrites two complementary approaches, one widely recognized and the other underappreciated in the field at large. While the cognitive science of religion (CSR) enjoys widespread recognition, the ethology of religion does not. This paper employs ethology to explain two submissive behaviours ritual practitioners often perform, that is, ocular aversion and rump presentation. Significantly, the means of submission reflect the practitioner's perceptions of the intimidating agents', e.g., deities', organ of intimidation. As it is in the animal kingdom, so too in the religious imagination, dominant others, especially males, will use their eyes or their phalluses to intimidate.